Wideband, Sand-Timer-Shaped Antenna for 5G mmWave and 28 GHz Applications - Soni, Devendra; Yadav, Dinesh; Tiwari, Manish (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This research paper introduces a novel, compact, and high-gain antenna design. The antenna, which has a shape resembling that of a sand timer, is specifically developed on a substrate made of Rogers/RT5880 material with a thickness of 0.8 mm. The proposed design exhibits a unidirectional radiation pattern, resulting in a wide impedance bandwidth of 9.18 GHz (ranging from 20.78 GHz to 29.96 GHz) and a gain of 5 dBi. The proposed design undergoes a transformation process and is afterwards evaluated through prototyping. A strong correspondence is observed between the measured and simulated data during the process of conducting measurements. The design exhibits a broader fractional bandwidth of 36.18% and a high-gain characteristic, rendering it well-suited for contemporary 5G millimeter-wave applications.